The Influence of the Atmosphere and the Location on Consumer Buying Interest in Kampung Kecil Restaurant of Bengkulu City - Faulia Faulia; Meiffa Herfianti; Andriyani Prawitasari (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the influence of the atmosphere and the location on consumer buying interest at Kampung Kecil Restaurant of Bengkulu City. The sample in this study was 65 consumers who bought at Kampung Kecil Restaurant of Bengkulu City. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the study show a positive regression direction with the equation Y = 7.005 + 0.512 (X1) + 0.295 (X2). The determination test is 0.826 or 82.6% of Buying Interest at Kampung Kecil Restaurant of Bengkulu City while the remaining 0.174 or 17.4% is influenced by other variables that are not included in this research model. The atmosphere has a significant influence on consumer buying interest at Kampung Kecil Restaurant of Bengkulu City, this is evidenced by the results of the t test showing a significant value of 0.001 is less than 0.05 meaning H0 is rejected and Ha is accepted. Location has a significant influence on consumer buying interest at Kampung Kecil Restaurant of Bengkulu City, this is evidenced by the results of the t test showing a significant value of 0.000 is less than 0.05 meaning H0 is rejected and Ha is accepted. Atmosphere (X1) and Location (X2) together have a significant influence on consumer buying interest (Y) at at Kampung Kecil Restaurant of Bengkulu City, this is evidenced by F test showing a significant value of 0.000 is less than 0.05.